Optimizing methyl‐eugenol aromatherapy to maximize posttreatment effects to enhance mating competitiveness of male Bactrocera carambolae (Diptera: Tephritidae). (11th November 2014) - Haq, Ihsan ul; Vreysen, Marc J.B.; Cacéres, Carlos; Shelly, Todd E.; Hendrichs, Jorge
Abstract Methyl‐eugenol (ME) (1, 2‐dimethoxy‐4‐(2‐propenyl)benzene), a natural phytochemical, did enhance male Bactrocera carambolae Drew & Hancock (Diptera: Tephritidae) mating competitiveness 3 d after ingestion. Enhanced male mating competitiveness can significantly increase the effectiveness of the sterile insect technique (SIT). ME application to mass reared sterile flies by feeding is infeasible. ME application by aromatherapy however, would be a very practical way of ME application in fly emergence and release facilities. This approach was shown to enhance mating competitiveness of B. carambolae 3 d posttreatment (DPT). Despite this added benefit, every additional day of delaying release will reduce sterile fly quality and will add cost to SIT application. The present study was planned to assess the effects of ME‐aromatherapy on male B. carambolae mating competitiveness 1DPT and 2DPT. ME aromatherapy 1DPT or 2DPT did enhance mating competitiveness of B. carambolae males whereas ME feeding 1DPT and 2DPT did not. Male mating competitiveness was enhanced by the ME aromatherapy irrespective if they received 1DPT, 2DPT or 3DPT. ME aromatherapy, being a viable approach for its application, did enhance mating competitiveness of male B. carambolae 1 d posttreatment as ME feeding did 3 d after ingestion.